2023
DOI: 10.1039/d2ob02305a
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Michael addition of malonates to β,γ-unsaturated α-ketoesters catalysed by Cu(ii) complexes bearing binaphthyl–proline hybrid ligands

Abstract: High yields (up to 96%) and high ee’s (up to 92%) were achieved for chiral copper (II) complex-catalysed enantioselective Michael addition of malonates to β,γ-unsaturated-α-ketoesters. The chiral ligands took the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…While chiral ligand L1 without the 3-CF 3 group induced Henry reaction products with (R)-configurations in up to 93% ee, chiral ligand L7 bearing the 3-CF 3 group induced Henry reaction products with (S)-configurations in up to 94% ee. 24 Such chiral ligands were also effective in the enantioselective reaction of different β,γunsaturated α-ketoester-related reactions, leading to the formation of different indole derivatives in up to 99% ee. 25 To further explore the application potential of chiral ligands L1−L7, enantioselective conjugate addition of 4-hydroxycoumarin 1a to β,γ-unsaturated α-ketoester 2a was tested as the model reaction.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While chiral ligand L1 without the 3-CF 3 group induced Henry reaction products with (R)-configurations in up to 93% ee, chiral ligand L7 bearing the 3-CF 3 group induced Henry reaction products with (S)-configurations in up to 94% ee. 24 Such chiral ligands were also effective in the enantioselective reaction of different β,γunsaturated α-ketoester-related reactions, leading to the formation of different indole derivatives in up to 99% ee. 25 To further explore the application potential of chiral ligands L1−L7, enantioselective conjugate addition of 4-hydroxycoumarin 1a to β,γ-unsaturated α-ketoester 2a was tested as the model reaction.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The O,N,O-type chiral ligands showed important application in enantioselective addition of diethylzinc to different aldehydes and enantioselective arylation of different aromatic aldehydes . Further replacing the hydroxyl group with the nitrogen group led to new O,N,N-type chiral ligands L1 – L7 , which gave promising results in different asymmetric catalytic reactions such as asymmetric Henry reactions and enantioselective addition of different nucleophiles to β,γ-unsaturated α-ketoesters . Preliminary study showed that the 3-CF 3 group in the chiral ligands played an important role in governing the enantioselection as well as in improving the enantioselectivity of the reactions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, we showed that a class of O–N–N tridentate ligands L1–L8 from BINOL and proline can be used in enantioselective addition of different nucleophiles to aldehydes 14 and β,γ-unsaturated α-ketoesters. 15 …”
mentioning
confidence: 99%